2009
DOI: 10.2323/jgam.55.171
|View full text |Cite
|
Sign up to set email alerts
|

Medium optimization by orthogonal array and response surface methodology for cholesterol oxidase production by Streptomyces lavendulae NCIM 2499

Abstract: This paper deals with the optimization of culture conditions for the production of cholesterol oxidase (COD) by Streptomyces lavendulae NCIM 2499 using the one-factor-at-a-time method, orthogonal array method and response surface methodology (RSM) approaches. The one-factor-at-a-time method was adopted to investigate the effects of medium components (i.e. carbon and nitrogen) and environmental factors (i.e. initial pH) on biomass growth and COD production. Subsequently, an L12 orthogonal matrix was used to eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 23 publications
1
22
2
Order By: Relevance
“…RSM optimization has been applied to investigate the interrelationship between different medium components affecting the cell growth and production kinetics of many industrially microbial products [16,20]. Furthermore, the obtained RSM optimization results are in good consistency with those previously reported for medium optimization by RSM for cholesterol oxidase production [37,38]. e authors optimized medium composition by RSM approaches for CO production by S. badius and S. lavendulae NCIM 2499. e authors were able to achieve an increase in volumetric enzyme production by 2.48 and 2 times their initially used production media.…”
Section: Validation Of the Modelsupporting
confidence: 57%
“…RSM optimization has been applied to investigate the interrelationship between different medium components affecting the cell growth and production kinetics of many industrially microbial products [16,20]. Furthermore, the obtained RSM optimization results are in good consistency with those previously reported for medium optimization by RSM for cholesterol oxidase production [37,38]. e authors optimized medium composition by RSM approaches for CO production by S. badius and S. lavendulae NCIM 2499. e authors were able to achieve an increase in volumetric enzyme production by 2.48 and 2 times their initially used production media.…”
Section: Validation Of the Modelsupporting
confidence: 57%
“…Voelker and Altaba [37] recorded an increase in the production of cholesterol oxidase by organic nitrogen much greater than inorganic nitrogen. The reason is that organic nitrogen may contain the most types of growth factors and amino acids required for the microbial growth and could be immediately metabolized by cells, thereby supporting the cholesterol oxidase production [29].…”
Section: Optimization Of the Selected Significant Variables By Box-bementioning
confidence: 99%
“…While in contrast Moradpour et al reported that pH of 6.5 supported the maximum production of CHOx [53]. In another investigation by Chauhan et al an initial pH of 7.5 was found to be optimum for S. lavendulae for production of CHOx [54].…”
Section: Insights In Enzyme Researchmentioning
confidence: 86%
“…The reason for this may be because organic nitrogen source contains most types of amino acids and growth factors for the growth of bacterium that could be metabolized directly by cells, hence promoting CHOx production [54].…”
Section: Physico-chemical Parameters Affecting Enzyme Productionmentioning
confidence: 99%